Phenotypic and genetic parameter estimation of milk traits of Abergelle goat in Ethiopia - Abebe, Yeshiwas Walle; Meberatie, Wossenie Shibabaw; Wondie, Zeleke Tesema (International Journal on Food, Agriculture and Natural Resources, 2025)
Abstract—this study aimed to evaluate the production performance and genetic parameters of Abergelle goat milk traits in Addis Mender and Alquzu village, Wag-Himera, Amhara region, Ethiopia. Data on milk traits were collected from 2018 to 2023 by the Sekota Dryland Agricultural Research Center from farmer-managed goats in scale-up villages. The General Linear Model (GLM) in SAS was used to analyze phenotypic traits, while Wombat software estimated genetic parameters and breeding values. Milk traits analyzed included daily milk yield (ADMY), 90-day lactation yield (LMY90 days), and lactation length (LL).Fixed effects considered were dam parity, year of kidding, and season. Mean values for ADMY, LMY90 days, and LL were 302.6±6.68 g, 28.003±47.45 kg, and 9.4±0.23 weeks, respectively. Heritability estimates for ADMY, LMY, and LL were 0.08±0.005, 0.16±0.034, and 0.04±0.34, while repeatability estimates were 0.50, 0.23, and 0.06, respectively. These findings show   moderate variation in milk production traits within the population, suggesting selection as an effective tool for genetic improvement. The study highlights the importance of repeated measurements and fixed effects in designing a genetic improvement program for Abergelle goats. Results provide valuable baseline data for enhancing milk production traits in this breed.